Living with a genetic, undiagnosed or rare disease: A longitudinal journalling study through the COVID‐19 pandemic. (5th February 2022) - Byun, Malia; Feller, Hollie; Ferrie, Monica; Best, Stephanie
Abstract: Introduction: COVID‐19 changed the way we lived with uncertainty from the outset as the pandemic impacted every aspect of our lives from well‐being, socializing to accessing healthcare. For people in vulnerable populations, such as those with genetic, undiagnosed and rare disorders, the experience was heightened. Aim: The aim of this study was to identify how the rapidly changing COVID‐19 environment impacted the lives of the Genetic, Undiagnosed and Rare Disease community. Methods: From June 2020 to May 2021, we collected monthly open‐ended journals from people living in Australia with genetic, undiagnosed and rare disorders. Data analysis was deductive, using the Resilience Scale for Adults, and inductive using thematic analysis. Results: We recruited 29 people (average of n  = 9.7 submissions each month). Responses changed over the year, with initial journals focusing on the importance of developing new structures for day‐to‐day lives, while later journals started to focus on mental well‐being. Throughout the project, participants reported challenges in accessing health and social care that was compounded by fear and concern over being exposed to the virus. Later journals highlight inconsistent messaging for vaccinations for this vulnerable community. Discussion/Conclusion: In parallel with the waves of the COVID‐19 pandemic, there need to be waves of targeted support for vulnerable communities. The first support wave needs to focus on facilitating the identification of new frameworks to structure day‐to‐day lives. A later second wave needs to focus on mental well‐being and coping with isolation, while consistent communication relating to health and social care throughout was essential. Patient/Public Contribution: This study was co‐designed, co‐led and analysed with a patient support network.